Positive impact of dynamic seeding of mesenchymal stem cells on bone-like biodegradable scaffolds with increased content of calcium phosphate nanoparticles - Sauerova, Pavla; Suchy, Tomas; Supova, Monika; Bartos, Martin; Klima, Jiri; Juhasova, Jana; Juhas, Stefan; Kubikova, Tereza; Tonar, Zbynek; Sedlacek, Radek; Piola, Marco; Fiore, Gianfranco Beniamino; et al. (Molecular biology reports, 2019)
One of the main aims of bone tissue engineering, regenerative medicine and cell therapy is development of an optimal artificial environment (scaffold) that can trigger a favorable response within the host tissue, it is well colonized by resident cells of organism and ideally, it can be in vitro pre-colonized by cells of interest to intensify the process of tissue regeneration. The aim of this study was to develop an effective tool for regenerative medicine, which combines the optimal bone-like scaffold and colonization technique suitable for cell application. Accordingly, this study includes material (physical, chemical and structural) and in vitro biological evaluation of scaffolds prior to in vivo study. Thus, porosity, permeability or elasticity of two types of bone-like scaffolds differing in the ratio of collagen type I and natural calcium phosphate nanoparticles (bCaP) were determined, then analyzes of scaffold interaction with mesenchymal stem cells (MSCs) were performed. Simultaneously, dynamic seeding using a perfusion bioreactor followed by static cultivation was compared with standard static cultivation for the whole period of cultivation. In summary, cell colonization ability was estimated by determination of cell distribution within the scaffold (number, depth and homogeneity), matrix metalloproteinase activity and gene expression analysis of signaling molecules and differentiation markers. Results showed, the used dynamic colonization technique together with the newly-developed collagen-based scaffold with high content of bCaP to be an effective combined tool for producing bone grafts for bone implantology and regenerative medicine.
Keywords: buněčná diferenciace; regenerativní lékařství; Tissue Engineering; Calcium Phosphates; Nanoparticles; Static cultivation; osteogeneze; tkáňové inženýrství; Osteogenesis; Mesenchymal Stem Cell Transplantation; Female; Bone and Bones; fosforečnany vápenaté; Tissue Scaffolds; kosti a kostní tkáň; kolagen; zvířata; Cells, Cultured; Collagen; Swine; Mesenchymal stem cells; transplantace mezenchymálních kmenových buněk; ženské pohlaví; tkáňové podpůrné struktury; Mesenchymal Stem Cells; mezenchymální kmenové buňky; kultivované buňky; Collagen scaffolds; Cell Differentiation; nanočástice; Dynamic seeding; Bone tissue engineering; Animals; Regenerative Medicine; prasata